Sistem Manajemen Rumah Sakit SUB-Sistem Penanganan Medis Pasien Rawat Jalan Menggunakan Aplikasi Java Server dan SMS Based Client - Fidelia, Theodora Anita; Somantri, Maman; Isnanto, R. Rizal (Transmisi, 2011)
Technology exists to provide easiness to a problem faced by society. One technology that is widely used and very popular by mobile phone users today are SMS (Short Message Service). With SMS, has been widely implemented applications that are based on current SMS, such as the Marquis, polls, forums, and even also for business applications such as ordering goods. So by utilizing technology that is being developed at this time, built a hospital information service to facilitate the public or the user who want to know information services at a hospital quickly, easily and inexpensively, which is built with the use of computer technology and mobile phones that can be provide interactive information between hospitals and the user. Writing Final Project Report is to design a Hospital Management System sub-systems Outpatient Medical Treatment based on SMS Client using Java server on Regional General Hospital Bekasi in detail, fast and up to date with the help of mobile phones as a medium of communication. In this thesis the design of Java programs and SMS Based Client Server uses Java as its programming language and database used is MySQL. Research methodology used in this study using a methodology RAD (Rapid Application Development) by using a development framework GRAPLLE (Guidelines for Rapid Application Engineering), grapple methodology is requirement planning segment, segment analysis and design segments. In this report will model the system software using UML. UML design model shows only the needs of the proposed system in an objective, particularly for computerized systems. Besides designing the new system is also done by arranging Final design is about the design of System Management Outpatient Medical Treatment based on SMS Client using Java server on the Board of the Regional General Hospital in Bekasi. The design of the system this information will assist in the processes of Outpatient Medical Management Services. This application can provide service to the community through the delivery of SMS in accordance with the format specified and the application can also automatically send a reply SMS in accordance with the information requested by the community, and earnings information quickly and on time according to the needs of system users. These applications are built, providing service to the community ten of them are patient registration services, the service queue to the poly, specialist information services, information services physician practice schedule, the total cost of service information, suggestions and complaints services, patient information services, information services empty room availability, room information services, information booking services inpatient rooms. Keyword : Hospital Management System, Medical Outpatient Treatment, Java, UML, MySQL.